Planning Effective Instruction, 6th Edition - Kay M. Price; Karna L. Nelson (Cengage Learning, 2018)
PLANNING EFFECTIVE INSTRUCTION: DIVERSITY RESPONSIVE METHODS AND MANAGEMENT, 6th Edition, fully equips you to teach in ways that meet the needs of all students in today's diverse classroom. Organized around a framework that guides you in focusing your efforts to plan for diversity, the book helps you see that what you teach, how you teach, and the context for teaching interact to bring about the success of all students. An appendix includes many sample lesson and activity plans for study and for use in your future classroom. As you read this book -- which integrates InTASC Standards and includes learning objectives -- you will find many resources and exercises that both lay the foundation for your future work and prove useful as tools that you can reference throughout your teaching career.